Urbanismo participativo. Construcción social del espacio urbano (2016)
A common denominator of the problems of cities is the conception of large urban projects that are designed under self-interested policies. These respond to a physical environment that needs to be transformed, but almost always fails to recognize the real needs of citizens. The purpose of this article is to review the alternatives that, for some decades now, have been explored as a strategy to implement urban transformations that are agile and democratize citizen participation. This is how inclusive cities come to be the result of a collective construction, they are accessible and have a vision of sustainability. This paper addresses through a literature review, three stages: first, the legislation refers to citizen participation in urban transformation processes in Colombia is reviewed; then there is a research on participatory planning as a new alternative for the transformation of the city and, at the end, an approach to the concept of crowdsourcing as philosophy and tools for participatory planning is done. The document will reveal this new form of urban management, which materializes in flexible and immediate solutions important for citizens who need to be included in the construction of the urban space in which their lives unfold daily.